Comparative expression profile of CD10 and cyclin D1 in cutaneous histiocytofibroma and dermatofibrosarcoma. Issue 4 (4th July 2021) - Kouki, Nadia; Ben Rejeb, Sarra; Cherif, Ines; Ghozzi, Amen; Chelly, Ines; Bellil, Khadija; Haouet, Slim
ABSTRACT: Dermatofibrosarcoma protuberans (DFSP) and histiocytofibroma (HF) are two rare fibrohistiocytic tumors, with some overlapping pathologic features. Immunohistochemistry is very useful in these cases. CD34 is a commonly used marker. However, the increasing cases of CD34 negative DFSP make it pressing to test other immunohistochemical markers that could help in the differential diagnosis. DFSP is known to harbor COL1A1-PDGFB rearrangement. Tumors in the differential diagnosis of DFSP usually lack this molecular signature. Recent studies suggested the interaction of PDGFB and PDGF receptor b with various signaling pathways, including the Akt-mTOR pathway. Cyclin D1, one of the oncoproteins activated in this pathway, may represent a promising useful biomarker in the differential diagnosis. On the other hand, CD10 expression in specialized mesenchymal skin cells, and especially in fibrohistiocytic skin tumors has been reported, which raises the interest of using this biomarker in HF and DFSP. In this study, we aimed to compare the expression of CD10 and cyclin D1 in 15 cases of DFSP and 15 cases of HF and discuss their potential contribution in the differential diagnosis.